Cold Air Drainage West of Fort Nelson, British Columbia - Harris, Stuart A. (ARCTIC, 1982)
In the early mornings of 7, 22 and 23 January 1982, intense cold air drainage was observed in the valleys on the eastern slopes of the Rocky Mountains west of Fort Nelson, British Columbia. Temperature differences of 31 degrees C were noted, the coldest temperature recorded being -71 degrees C (a new North American record), though even colder temperatures probably occurred at other sites. These were produced by an intense cold arctic high-pressure cell which gave regionally still air and clear skies and permitted marked local cooling during the nights. Similar conditions should be expected elsewhere along the slopes of the Rocky Mountains in northern B.C. and southern Yukon Territory.